Dancing Naturally
XI, 179 p.
Keywords: A renewed interest in nature, the ancient Greeks, and the freedom of the body was to transform dance and physical culture in the early twentieth century. The book discusses the creative individuals and developments in science and other art forms that shaped the evolution of modern dance in its international context.